Stress and Food Preferences: A Lab Experiment with Low-SES Mothers - Michèle Belot; Jonathan James; Martina Vecchi; Nicolai Vitt (Institute of Labor Economics (IZA), 2019)
We investigate whether short-term everyday stressors leads to unhealthier dietary choices among low socioeconomic status mothers. We propose a novel stress protocol that aims to mimic everyday stressors experienced by this population, involving time and financial pressure. We evaluate the impact of stress on immediate and planned food choices, comparing a group exposed to our stress protocol relative to a control group. Immediate consumption is measured with in-laboratory consumption of low calorie and high calorie snacks; planned consumption is measured with an incentivized food shopping task. The stressfulness of the stress protocol is evaluated using subjective assessments, as well as physiological measurements (heart rate and salivary cortisol levels). We find no evidence of an effect of stress on the nutritional content of immediate or planned food consumption, thus no support for the hypothesis that everyday stressors are a likely explanation for unhealthy food choices.
Keywords: I12; D91; 330; diet; acute stress; everyday stressors; lab experiment